Entrepreneurship, Entry and Performance of New Businesses Compared in two Growth Regimes: East and West Germany - Michael Fritsch (Max Planck Institute for Research into Economic Systems, 2004)
The paper provides an outline of the concept of regional growth regimes and empirically illustrates the relevance of the concept. The empirical examples are entrepreneurship, entry and the performance of new businesses in East and West Germany. The differences of the factors determining the formation of new businesses as well as their development between these two growth regimes are immense and clearly demonstrate the relevance of region specific factors.
Keywords: R11; P25; O18; O11; 330; Growth regimes; New business formation; New business performance; Location; Regional influences; Unternehmer; Unternehmensgründung; Markteintritt; Erfolgsfaktor; Standortfaktor; Region; Alte Bundesländer; Neue Bundesländer; Deutschland